(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Regulation (EU) 536/2014 abrogates Directive 2001/20/EC of the European Parliament and of the Council and was created with the aim of centralizing and optimizing the process of evaluation of clinical trials in Europe. The innovations directly or indirectly introduced by the Regulation 536/2014 intervened on the progressive involvement of patients and lay persons in research. Such implications, of ethical relevance, will be explored in this contribution in relation to the theme of the composition of the ethics committees, the independence required by the Regulation, and the dissemination of clinical trials results.